ANTIBACTERIAL EFFICACY OF ALLIUM SATIVUM AGAINST MULTIDRUG-RESISTANT BACTERIAL PATHOGENS AND ITS SYNERGISTIC INTERACTION WITH CONVENTIONAL ANTIBIOTICS - Tuamah, Mustafa Raheem (Antis-Publisher, 2025)
Objective: This study aims to investigate the potential of Allium sativum (garlic) as an alternative antibacterial agent in the context of rising antibiotic resistance. Method: A comprehensive literature review was conducted, focusing on in vitro and in vivo studies that evaluate the antimicrobial efficacy of Allium sativum against multidrug-resistant (MDR) bacterial strains. Sources included peer-reviewed journals in microbiology, pharmacology, and ethnomedicine. Results: The analysis reveals that Allium sativum exhibits broad-spectrum antibacterial activity, particularly effective against Gram-positive and Gram-negative MDR bacteria. Its bioactive compounds, such as allicin, disrupt bacterial cell walls, inhibit enzyme activity, and prevent biofilm formation. The low incidence of side effects and the affordability of garlic make it a viable candidate for complementary or integrative antimicrobial therapies. Novelty: This study highlights the relevance of traditional medicinal plants in modern antimicrobial drug discovery, emphasizing Allium sativum as a sustainable, natural, and accessible alternative in combating antibiotic-resistant infections, with implications for public health and pharmaceutical innovation.